Do menstrual cups increase risk of IUD expulsion? A survey of self-reported IUD and menstrual hygiene product use in the United States. (3rd September 2019) - Schnyer, Ariela N.; Jensen, Jeffrey T.; Edelman, Alison; Han, Leo
Abstract: Purpose: To gather preliminary data about menstrual hygiene product use and associated risk of intrauterine device (IUD) expulsion. Materials and methods: We conducted an Internet-based survey using the Amazon Mechanical Turk (MTurk) platform and Researchmatch.org. Eligible participants were women at least 18 years old and self-identified as current or previous IUD users. Results: Of 902 survey responses, 71% reported current or previous IUD use and 19.7% reported menstrual cup use. IUD users were significantly more likely than non-IUD users to use a menstrual cup or tampons. Among all IUD users, 56 individuals reported experiencing at least one expulsion (8.8%). We found a positive association between concurrent menstrual cup use and IUD expulsion (OR: 2.75, 95% CI: 1.40–5.42, p = .002), but no association with concurrent tampon or pad use. Of concurrent IUD and cup users who experienced an expulsion, one reported it occurring 'while using a menstrual cup', with others reporting the expulsion during other events. Conclusions: Menstrual cup use may be higher than previously reported, particularly in IUD users. Concurrent menstrual cup use may increase the risk of IUD expulsion. Prospective research is necessary to fully explore the relationship between menstrual hygiene product use and IUD expulsions.